(untitled) (London Journal of Engineering Research, 2022)
Polycrystalline of BaNix-2ZnxFe16O27 (where x = 0.0,0.4,0.8,1.2,1.6, and 2.0), hexagonal ferrites samples were synthesized by using the conventional standard ceramic method. Fourier Infrared (FITR) Spectroscopy analysis was used to investigation the structural parameters of the samples. FTIR spectra of the samples have been analyzed in the frequency range (400-4000) cm-1 . The result shows that the two main bands of absorption corresponding to tetrahedral ν1 and octahedral ν2 were observed, which illustrated the formation of the ferrite phase. The high-frequency band in the range 550-600 cm1 and a low-frequency band at around 400 cm-1 were assigned to tetrahedral ν1 and octahedral ν2 sites, respectively. The force constants (FCons) were calculated for tetrahedral Ftet sites and octahedral Foct sites and were found to decrease with increasing Zn ions. Debye temperature (θD) also, has been estimated as a function of composition at room temperature using FTIR spectra.